2019
DOI: 10.1039/c9nj01434a
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon aerogel supported copper catalysts for the hydrogenation of methyl acetate to ethanol: effect of KOH activation

Abstract: Methyl acetate (MA) hydrogenation is crucial for indirect ethanol synthesis through syngas (CO + H2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…11), due to the fact that Cu-based catalysts are active for the hydrogenation of the C=O bond while much less active for the cleavage of the C−C bond. 398,410 Although a Nibased catalyst was also developed, 411 the desired product yield was not high, compared with Cu-based catalysts (Table 11, entry 18). Similar with the situation in oxalate hydrogenation, the valence state of Cu species is one of the most important factors influencing the catalytic performances.…”
Section: Reaction Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…11), due to the fact that Cu-based catalysts are active for the hydrogenation of the C=O bond while much less active for the cleavage of the C−C bond. 398,410 Although a Nibased catalyst was also developed, 411 the desired product yield was not high, compared with Cu-based catalysts (Table 11, entry 18). Similar with the situation in oxalate hydrogenation, the valence state of Cu species is one of the most important factors influencing the catalytic performances.…”
Section: Reaction Networkmentioning
confidence: 99%
“…hydrogenation of CO to ethanol, has disadvantages like low CO conversion and low ethanol selectivity, restricting its industrial application. 398 Hence, the indirect route becomes attractive because of its potentially higher yield of ethanol. Here we take methyl acetate as an example to illustrate the reaction network, as described in Scheme 13.…”
Section: Reaction Networkmentioning
confidence: 99%
“…Luckily, aerogel‐based graphitics such as graphene or CNTs can be skipped as they are graphitized. Physically or chemically, carbon aerogels with potassium hydroxide (KOH), sodium hydroxide (NaOH), carbon dioxide (CO 2 ), and water (H 2 O) have been activated to produce extra micropores and increase the surface area 51,52 . Furthermore, several parameters, such as surface area, pores, and product pore size distribution, will be controlled by the activation of carbon aerogel 53 …”
Section: Production Methodsmentioning
confidence: 99%
“…Physically or chemically, carbon aerogels with potassium hydroxide (KOH), sodium hydroxide (NaOH), carbon dioxide (CO 2 ), and water (H 2 O) have been activated to produce extra micropores and increase the surface area. 51,52 Furthermore, several parameters, such as surface area, pores, and product pore size distribution, will be controlled by the activation of carbon aerogel. 53 F I G U R E 3 Different procedures to prepare aerogel and aerogel composite-based catalysts 47…”
Section: Carbonizationmentioning
confidence: 99%
“…On the other hand, subsequent studies considered both Cu + and Cu 0 as active sites in the catalytic hydrogenation of carbon–oxygen bonds. It is widely believed that the synergistic effect of Cu 0 and Cu + could improve the catalytic hydrogenation activity, suggesting Cu 0 activates H 2 and Cu + activates the methoxy (CH 3 O−) and acyl (CH 3 CO−) group. ,, Some studies reported the synergistic effect of Cu 0 and Cu + on the catalytic hydrogenation of DMO, in which the incorporation of a suitable amount of promoters (La, Ag, Au, B) was reported to enhance the catalytic activity and stability of the Cu/SiO 2 catalyst. It is suggested that the coexistence of Cu + and Cu 0 sites in the proper distribution on the catalyst surfaces is vital for the hydrogenation of C–O bonds.…”
Section: Copper-based Catalysts For Hydrogenation Of Co2-derived Ethy...mentioning
confidence: 99%